RNAi and microRNA-Mediated Gene Regulation in Stem Cells Methods, Protocols, and Applications - Zhang, Baohong.; Zhang, Baohong.; Stellwag, Edmund J.; Stellwag, Edmund J. (Methods in Molecular Biology, 2010)
Recent stem cell research has revealed that miRNA and RNAi-mediated gene regulation is one of the vital determinates controlling the state of cell differentiation, with the small RNAs serving as key elements involved in regulatory network control of pluripotent cell fate determination. In RNAi and microRNA-Mediated Gene Regulation in Stem Cells: Methods, Protocols, and Applications, expert authors from laboratories across the globe contribute an accessible compendium of up-to-date, proven methods focused on the study of the titular topic. Divided into three sections, the book first gives a brief introduction to RNAi and miRNAs in stem cells, with a focus on the current status of research and future perspectives, then it continues with detailed methods and protocols for RNAi screening, transfection, and the knockdown of specific genes and pathways in several animal species, including humans and mice, concluding with a section on recently developed methods for identification of miRNAs, including a general protocol for preparation and analysis of miRNA libraries for deep sequencing, knock down of a specific gene using miRNA-based shRNA, and miRNA expression analysis using qRT-PCR. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes highlighting tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, RNAi and microRNA-Mediated Gene Regulation in Stem Cells: Methods, Protocols, and Applications serves as a valuable resource for scientists and aspiring graduate students interested in the intersection of RNAi, miRNA, and stem cell molecular biology and the exciting areas of medicine, including regenerative medicine, aging, cancer, and neurological disorders, that can be advanced through this expanding area of research.